The exacerbating effects of stable pulmonary tuberculosis on the deterioration of inflammatory response, coagulation function, and pulmonary function in COPD: A propensity score-matched retrospective study - Jiangbo Li; Mei Ye; Haiyue Wang; Aidibai Ainiwaier; Ayididar Jumahan; Feng Sun (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases, 2025)
Chronic obstructive pulmonary disease (COPD) and tuberculosis pose significant public health challenges, particularly in tuberculosis-endemic developing regions where their co-prevalence may exacerbate the disease burden of chronic airflow obstruction. This study aimed to investigate the impact of stable pulmonary tuberculosis on inflammatory status, coagulation function, and pulmonary function in COPD patients during acute exacerbations.We conducted a retrospective analysis of 68 COPD patients with acute exacerbation and stable pulmonary tuberculosis (observation group) admitted between December 2019 and December 2023. Using propensity score matching based on age and gender, we selected 68 COPD patients without stable pulmonary tuberculosis as the control group. Comparative analysis of laboratory tests and pulmonary function parameters revealed that the observation group had significantly elevated levels of erythrocyte sedimentation rate (ESR), interleukin-6 (IL-6), lymphocyte count, platelet count (PLT), and D-dimer, along with significantly reduced pulmonary function parameters including forced expiratory volume in 1 s/forced vital capacity (FEV1/FVC) and forced expiratory flow between 25 %-75 % of vital capacity (FEF25-FEF75) (all P < 0.05). Correlation analysis demonstrated positive associations between ESR/IL-6 levels and D-dimer, PLT, and fibrin(ogen) degradation product (FDP) levels (P < 0.05).Binary logistic regression analysis of 14 significantly different variables identified IL-6 (OR = 1.056), ESR (OR = 1.022), PLT (OR = 1.005), D-Dimer (OR = 1.002), FEV1/FVC (OR = 0.962), FEF50 (OR = 0.534), and FEF75 (OR = 0.089) as independent factors associated with acute exacerbation in COPD patients with stable pulmonary tuberculosis (all P < 0.05). Our findings indicate that elevated IL-6, ESR, PLT, and D-Dimer levels coupled with decreased FEV1/FVC, FEF50, and FEF75 levels represent distinctive clinical characteristics of these patients.This study demonstrates that COPD patients with stable pulmonary tuberculosis exhibit enhanced inflammatory responses, prothrombotic tendencies, and more severe pulmonary function impairment, providing a scientific basis for developing individualized treatment strategies for this patient population.